2021
DOI: 10.1111/jocn.15798
|View full text |Cite
|
Sign up to set email alerts
|

Exploring newly qualified nurses’ experiences of support and perceptions of peer support online: A qualitative study

Abstract: Aims and Objectives: To explore newly qualified nurses' support needs and their perceptions of online peer support. Background:The experience of being a newly qualified nurse is stressful and isolating. Support from colleagues and peers can enhance perceptions of competence and confidence in newly qualified nurses, improve well-being and aid retention. However, despite initiatives such as preceptorship, support needs may remain unmet in busy clinical environments. Online support has potential to offer a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Whilst participants were aware of such services, they did not align to their needs. Similarly to previous research, 6365,6772 sourcing peer support (i.e. support provided by healthcare assistants to other healthcare assistants) was reported as helping to cope with the emotional challenges of practice coupled with a positive impact on the care provided, while enhancing competence, confidence and building participants’ resilience.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Whilst participants were aware of such services, they did not align to their needs. Similarly to previous research, 6365,6772 sourcing peer support (i.e. support provided by healthcare assistants to other healthcare assistants) was reported as helping to cope with the emotional challenges of practice coupled with a positive impact on the care provided, while enhancing competence, confidence and building participants’ resilience.…”
Section: Discussionsupporting
confidence: 61%
“…support provided by healthcare assistants to other healthcare assistants) was reported as helping to cope with the emotional challenges of practice coupled with a positive impact on the care provided, while enhancing competence, confidence and building participants' resilience. [70][71][72] Further research on peer support among healthcare assistants is especially important in the context of risks associated with not accessing formal support and potential underreporting of risks 30-32 hiding true exposure of risks among this cohort. It is also important to understand, when support or guidance offered by peers may contribute to increased risks for the lone worker, patients, families and the organisations in the absence of relevant training.…”
Section: Main Findingsmentioning
confidence: 99%
“…In contrast, this study's findings indicate that while mentally and emotionally challenged, the NQNs embraced the unique learning and developmental opportunities which arose. Pre‐pandemic research shows that as NQNs become more familiar with their role, their confidence grows and anxiety lessens (Jenkins et al, 2021). In keeping with findings of other research, participants had already been challenged by situations ‘beyond their level of readiness’ (RCN, 2021b, p. 12) which seemed to accelerate their transition, build confidence and ameliorate some of the known negative effects of transition.…”
Section: Discussionmentioning
confidence: 99%
“…Their foremost recommendation is to prioritise the well‐being of staff, proposing that those who worked through the pandemic be given ‘time, space and resources to recover’ and to address the drivers of poor staff experience and chronic excessive workloads. We now have an opportunity to harness some of the innovations that were successful during the pandemic, for example the positive potential for online preceptorship peer support (Jenkins et al, 2021). The switch to online teaching as well as the use of social media to provide both peer and professional support as part of preceptorship for NQNs was highly valued, supporting the need for the ongoing use of these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[43] Current literature suggested that peer support has a direct alleviating effect on depression, [44] and can alleviate workplace anxiety and improve job satisfaction. [45] Thus, the head nurse of the department should encourage a welcoming department atmosphere, implement early humanistic care, talk to nurses more often, and meet nurses' personal needs under reasonable premises, such as offering free yoga classes and guidance on infant feeding to relieve the anxiety of returning nurses. Hospitals can also implement programs targeted towards the maintenance of nurses' mental health, such as on-site counsellors and buddy teams that check in on each other.…”
Section: Physiological Needsmentioning
confidence: 99%